2015
DOI: 10.3390/pathogens4030682
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to Human Metapneumovirus Infection: What We Have Learned from the Mouse Model

Abstract: Human Metapneumovirus (hMPV) is a leading respiratory viral pathogen associated with bronchiolitis, pneumonia, and asthma exacerbation in young children, the elderly and immunocompromised individuals. The development of a potential vaccine against hMPV requires detailed understanding of the host immune system, which plays a significant role in hMPV pathogenesis, susceptibility and vaccine efficacy. As a result, animal models have been developed to better understand the mechanisms by which hMPV causes disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 72 publications
(106 reference statements)
0
14
0
Order By: Relevance
“…However, our study involved inpatients with severe lower airway infections, and IL-1β and IL-6 levels were higher in the hMPV group, unlike in study of Laham et al [ 15 ]. hMPV infection in mice has been shown to induce increased levels of IL-6 compared to those infected with RSV [ 16 ]. A study by Guerrero-Plata et al [ 17 ] found human dendritic cells exposed to hMPV and RSV produced increased levels of IL-6 and IL-1B.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study involved inpatients with severe lower airway infections, and IL-1β and IL-6 levels were higher in the hMPV group, unlike in study of Laham et al [ 15 ]. hMPV infection in mice has been shown to induce increased levels of IL-6 compared to those infected with RSV [ 16 ]. A study by Guerrero-Plata et al [ 17 ] found human dendritic cells exposed to hMPV and RSV produced increased levels of IL-6 and IL-1B.…”
Section: Discussionmentioning
confidence: 99%
“…Innate immune responses are the first line of defence against the viral infection and act by recognizing the pathogen associated molecular patterns (PAMPS) on the viral particles through the pattern recognition receptors (PRRs) present on the immune cells in the respiratory tracts. The common PRRs like membrane bound Toll-like-receptors (TLRs), C-type lectin receptors (CLRs), cytoplasmic RIG-I like receptors (RLRs) and nucleotide-binding oligomerization domain (NOD) like receptors (NLRs) recognize the viral PAMPs and initiate the inflammatory and immune response via the cytokines produced by the cells in respiratory tract [ 19 ]. MyD88 (common adaptor of TLRs) mediated pathways has been shown to be essential for pulmonary immune response to HMPV infection by recruitment of immune cells to lungs [ 83 ].…”
Section: Immune Response To Hmpvmentioning
confidence: 99%
“…During HMPV infection, the protective humoral immunity is mostly directed towards the F protein of the virus rather than G and SH proteins [ 35 ]. The cell mediated immune response is majorly responsible for immune surveillance in the infected host and clears the virus infection by activation of virus specific cytotoxic T lymphocytes (CTLs) which induces the apoptosis of infected cells or by activating the Th cells to further activate B cells and other immune cells like DCs and macrophages [ 19 ]. Studies done on mice models indicate that during HMPV primary infection, CD4 + as well as CD8 + T cells are responsible for inflammation and body weight loss leading to severe lung disease but they also have a protective role of clearing the virus infection from the host’s body which is evident by accumulation of HMPV specific CTLs in the lungs of infected host at approximately 7 days post infection [ 2 , 43 , 54 ].…”
Section: Immune Response To Hmpvmentioning
confidence: 99%
“…By 5 yr old, most children have been infected by HMPV, and by the age of 25, virtually all adults have been exposed to the virus [26,27]. Research studies conducted over the last decade demonstrate that HMPV induces a spectrum of immune responses, some of which contribute to the antiviral defense, whereas others mount an evasion strategy by the virus for effective infection [28,29]. However, several gaps in the understanding of immune responses to HMPV resulted in limited success with the development of effective vaccines and specific therapeutics against this clinically important viral infection.…”
Section: Introductionmentioning
confidence: 99%